The fragmentation of Indonesian film audience - Suwarto, Dyna Herlina; Setiawan, Benni; Adikara, Gilang Jiwana (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nowadays, films can not only be watched in conventional media such as cinema, screening and television but also digital media such as streaming, download and shared archives. This study aims to determine the pattern of audience fragmentation, especially in the cinephile segments. The research employs an explorative qualitative method. The data collection methods include diaries and interviews. Informants were determined using a purposive sampling technique which includes visitors of the movie screened by the Jogja Movie Night, DIY Watching Club, and Cultural Department in July 2018. The results of this study show that, first, conventional media such as cinema and screening are still considered important because they provide a tasting guide, a space for social interaction and technical facilities. Second, attention is managed differently when dealing with conventional and new media. The focus of watching a movie can be created in different ways tailored to the viewing space. Third, film content is used as inspiration to produce films as hobbies and learning space. Also, it can be diverted in other forms such as short stories, performance scripts. Although being exposed to unlimited choices, film viewers only access the relative channels for a certain period. They need public space to interact with film fans, educate their appetite and watch satisfaction. Digital media is used to facilitate the autonomy of choosing and treating films based on their needs and desires.